The development and psychometric testing of three instruments that measure person‐centred caring as three concepts – Personalization, participation and responsiveness. (25th August 2020) - Strachan, Heather; Williamson, Laura; Elders, Andrew; Sutherland, Ben; Hibberd, Carina; Williams, Brian
Abstract: Aim: To develop and test the psychometric properties of three instruments that measure Person‐centred Caring: as Personalization, Participation and Responsiveness. Design: A three‐phase mixed methods design used two frameworks: content validity determination and quantification; consensus‐based standards for selection of health measurement instruments. Methods: A narrative literature review identified the domain definition. A systematic review of instruments provided the basis for item pools, which were refined by focus groups ( N  = 4) of multidisciplinary staff and service users ( N  = 25) and cognitive interviews ( N  = 11) with service users. Scale content validity indexes were calculated. Three cross‐sectional surveys were conducted between April 2015 and June 2016. The instruments' psychometric properties tested included factor structure, internal consistency and construct validity. Convergent validity was tested, hypothesizing that: Personalization related to relational empathy; Participation related to empowerment; and Responsiveness related to trust. Results: Scale content validity indexes were ≥0.96 in all instruments. Response rates were 24% ( N  = 191), 15% ( N  = 108) and 19% ( N  = 124). Two factors were revealed for the Personalization and Responsiveness instruments and one factor for the Participation instrument. All had acceptable: reliability (Cronbach's Alpha >0.7); construct validity (>50%); and convergent validity (Spearman's correlation coefficient >0.25, p  < 0.05). Conclusion: This study composed definitions and instruments that reflect the multidisciplinary teams' caring behaviours, which have acceptable reliability and validity in the community population. Further psychometric testing of Participation and Responsiveness instruments should be undertaken with a larger sample. Impact: The instruments can be used to monitor the variability of multidisciplinary teams' caring behaviours; research effective interventions to improve caring behaviours; and increase understanding of the impact of caring on health outcomes. 摘要: 目标: 开发并测试三种衡量以人为本的关怀工具的心理测量特性:个性化、参与性和响应性。 设计: 三阶段混合方法设计使用两个框架:内容效度测定和量化;基于共识的健康测量工具选择标准。 方法: 叙述性文献回顾确定了该领域定义。对工具的系统审查为项目库提供基础, 该项目库由多学科工作人员和服务用户组成的焦点小组(N=4)和对服务用户的认知访谈内容(N=11)加以完善。计算量表内容效度指标。2015年4月至2016年6月进行了三次横断面调查。测试工具的心理测量性质包括因子结构、内部一致性和结构效度。检验了收敛效度, 假设:与关系共情相关的个性化;与授权相关的参与性;与信任相关的响应性。 结果: 所有测量工具的量表内容效度指数均≥0.96。响应率分别为24%(N=191)、15%(N=108)和19%(N=124)。个性化和响应性工具有两个因素, 参与性工具有一个因素。所有均可接受:可靠性(信度系数>0.7)、结构效度(>50%)和收敛效度(斯皮尔曼相关系数>0.25.p<0.05)>。 结论: 本研究包含了反映多学科团队关怀行为的定义和工具, 在社区人群中具有可接受的信度和效度。参与性和响应性工具的进一步心理测量测试应采用更大的样本范畴。 影响: 这些工具可用于监测多学科团队护理行为的变量;研究改善护理行为的有效干预措施;增进对护理对健康结果影响的理解。